2023
DOI: 10.1038/s41586-023-05973-1
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid 2D–CMOS microchips for memristive applications

Abstract: Exploiting the excellent electronic properties of two-dimensional (2D) materials to fabricate advanced electronic circuits is a major goal for the semiconductor industry1,2. However, most studies in this field have been limited to the fabrication and characterization of isolated large (more than 1 µm2) devices on unfunctional SiO2–Si substrates. Some studies have integrated monolayer graphene on silicon microchips as a large-area (more than 500 µm2) interconnection3 and as a channel of large transistors (rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
90
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 32 publications
(28 reference statements)
1
90
0
Order By: Relevance
“…Two-dimensional (2D) layered materials have also been introduced as switching medium in memristors. The best resistive switching performance for memory and neuromorphic applications has been obtained in multilayer hexagonal boron nitride (h-BN) produced using chemical vapor deposition (CVD). The reasons are (i) h-BN is an insulator with a band gap ∼6 eV, meaning that it can block current in HRS and reduce energy consumption; and (ii) CVD provides the right amounts of native defects that enable stable RS. , A recent study reported crossbar arrays of small (<0.053 μm 2 ) h-BN memristors with high endurance (>5 × 10 6 cycles), and low energy consumption per state transition (∼1.41 pJ) . It has been studied that the switching occurs by metal penetration from the electrodes , as in ECM.…”
Section: Memristive Behaviors Of Various Materials and Devicesmentioning
confidence: 99%
“…Two-dimensional (2D) layered materials have also been introduced as switching medium in memristors. The best resistive switching performance for memory and neuromorphic applications has been obtained in multilayer hexagonal boron nitride (h-BN) produced using chemical vapor deposition (CVD). The reasons are (i) h-BN is an insulator with a band gap ∼6 eV, meaning that it can block current in HRS and reduce energy consumption; and (ii) CVD provides the right amounts of native defects that enable stable RS. , A recent study reported crossbar arrays of small (<0.053 μm 2 ) h-BN memristors with high endurance (>5 × 10 6 cycles), and low energy consumption per state transition (∼1.41 pJ) . It has been studied that the switching occurs by metal penetration from the electrodes , as in ECM.…”
Section: Memristive Behaviors Of Various Materials and Devicesmentioning
confidence: 99%
“…1 Among them, the fabrication of solid-state microelectronic devices and circuits made of 2D materials has attracted much attention, as it may be a solution to produce advanced electronic devices and circuits beyond the complementary metal-oxide-semiconductor (CMOS) technology. 2,3 However, most 2D material-based electronic devices consist of prototypes fabricated using methods that are not compatible with wafer-scale circuital technologies, such as mechanical exfoliation of small crystals. 4 Chemical vapor deposition (CVD) is a scalable method to produce large-area 2D materials; however, the CVD method requires the use of high temperatures >850 °C, which impedes the direct growth of the 2D material on wafers containing CMOS circuits.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, 2D materials, such as graphene, TMDs, and other members of the Xene family, excel in the context of scaled up to chip integration and offer enhanced performance. 9 Due to their unique atomic-layer structure, 2D materials possess exceptional electrical, optical, and mechanical properties. Their ultrathin nature allows for precise control over the device dimensions and properties, enabling better performance and more meaningful applications.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the band gap of atomically layer thick non-2D materials, such as Si or GaAs, would be far too large for most electronic applications. In contrast, 2D materials, such as graphene, TMDs, and other members of the Xene family, excel in the context of scaled up to chip integration and offer enhanced performance . Due to their unique atomic-layer structure, 2D materials possess exceptional electrical, optical, and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%